Lewis acidic zeolite Beta catalyst for the Meerwein–Ponndorf–Verley reduction of furfural. Issue 9 (9th December 2015) - Koehle, Maura; Lobo, Raul F.
Abstract : Tin-, zirconium- and hafnium-containing siliceous Beta zeolite were investigated in the Meerwein–Ponndorf–Verley reduction of furfural under continuous flow conditions. Abstract : The catalytic properties of tin-, zirconium- and hafnium-containing siliceous zeolite Beta were investigated in the Meerwein–Ponndorf–Verley reduction of furfural using a liquid-phase plug-flow microreactor at temperatures between 328–358 K. Catalytic rates varied widely with the highest turnover frequency observed on Hf-Beta (4.6 min −1 ), followed by Zr- and Sn-Beta (1.8 min −1 and 0.51 min −1, respectively). The lowest activation energy was observed on Hf-Beta (49.6 kJ mol −1 ) while Zr- and Sn-Beta showed higher but similar activation energy (60.7 and 60.4 kJ mol −1, respectively). The catalysts deactivate with time on stream (with a half-life of 3.5 hours or longer) and are poisoned by the reaction product furfuryl alcohol. Deactivation is caused partly by the polymerization of reactants and products that are retained in the zeolite pores and block access to active sites, but operation at higher temperature (408 K) slows the rate of deactivation significantly. The catalytic properties of the materials can be regenerated by calcination in air.